IOT-Based smart street lighting enhances energy conservation - Zakiah Mohd Yusoff; Zuraida Muhammad; Mohd Syafiq Izwan Mohd Razi; Noor Fadzilah Razali; Muhd Hussaini Che Hashim (Institute of Advanced Engineering and Science, 2020)
The electricity generation cost is escalating every year while the electric energy is indispensable and increasing in demand. The resources for energy generation is also depleting due to the increasing demand of power. Thus, a system that can reduce the energy wastage and the massive expenses is essential. Street light system is one of the systems that can reduce energy consumption. The massive energy consumption from the current street light system is not efficient enough to reduce the wasted energy. By implementing an IOT-based smart street light system, the power consumption of the street light will be optimized. This system will also provide the ability to monitor input voltage for Arduino MEGA 2560 microcontroller and control the street light through IOT. The concept of this smart system is to introduce an intelligent system which can decide to switch on or off the street light according to the movement detection by using an infrared sensor module. The data will be sent to Arduino Mega 2560, which is a microcontroller that will decide to turn on or off the street light. The Wi-Fi module ESP-01 is implemented to enable the microcontroller to connect to Blynk software for monitoring and controlling purpose. The result shows that the smart street light system is expected to reduce energy consumption up to 45.48% on weekdays and 32.22% on weekends from the present street light system which uses timer system. The IOT-based Smart Street Light system also shows the condition of the street light system based on the Blynk interfaces for maintenance purpose.